2006
DOI: 10.1002/ptr.1830
|View full text |Cite
|
Sign up to set email alerts
|

Effects of combining extracts (from propolis or Zingiber officinale) with clarithromycin on Helicobacter pylori

Abstract: Propolis and Zingiber officinale have been shown to be specifically targeted against Helicobacter pylori strains, to possess antiinflammatory, antioxidant and antitumoral activity and to be used in traditional medicine for the treatment of gastrointestinal ailments. Considering that these natural products could potentially serve as novel therapeutic tools also in combination with an antibiotic, the aim of this work was to evaluate their effect when combined with clarithromycin on clinical H. pylori isolates (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(54 citation statements)
references
References 27 publications
1
51
0
1
Order By: Relevance
“…It was found that gingerol inhibited the growth of H. pylori strains in vitro and this activity may contribute to its chemopreventive effects against colon cancer (Mahady et al, 2003). This anti-H. pylori action was further confirmed by Mahady et al (2005) and Nostro et al (2006). Recently, Weng et al (2010) demonstrated that [6]-shogaol and [6]-gingerol exerted anti-invasive activity against human hepatocarcinoma cells.…”
Section: Zingiber Officinale Roscoe Zingiberaceae (Gengibre)mentioning
confidence: 63%
“…It was found that gingerol inhibited the growth of H. pylori strains in vitro and this activity may contribute to its chemopreventive effects against colon cancer (Mahady et al, 2003). This anti-H. pylori action was further confirmed by Mahady et al (2005) and Nostro et al (2006). Recently, Weng et al (2010) demonstrated that [6]-shogaol and [6]-gingerol exerted anti-invasive activity against human hepatocarcinoma cells.…”
Section: Zingiber Officinale Roscoe Zingiberaceae (Gengibre)mentioning
confidence: 63%
“…officinale at a concentration of 2.5 mg/mL of fresh and glycolic extracts and 5.0 mg/mL of dried extract showed antimicrobial action against E. faecalis by protective action against experimental infection in G. mellonella. The exact antimicrobial mechanism by which Z. officinale acts on microorganisms still needs to be clarified (17). However, it may be anticipated that different action mechanisms of this phytotherapic that lead to microbial reduction may be partly due to its hydrophobicity.…”
Section: Discussionmentioning
confidence: 99%
“…pylori coloniza la mucosa gástrica de más de la mitad de la población mundial y es responsable de gastritis crónica, úlcera péptica, adenocarcinoma y linfoma asociado a la mucosa gástrica 7,10 . El tratamiento convencional sólo logra entre 70 y 80% de éxito en la cura de los pacientes, por lo que se busca activamente alternativas terapéuticas distintas a los antimicrobianos, como vacunas, probióticos, inactivación fotodinámica, fagoterapia y búsqueda de productos fitoterapéuticos o nutracéuticos [8][9][10][13][14][15][16] . Entre las alternativas fitoterapéuticas, destaca el potencial uso de los extractos de propóleos, que están constituidos por flavonoides, ácidos fenólicos y sus ésteres, además de una gran variedad de otros compuestos cuya presencia y cantidad varía según el lugar de obtención 1,2 .…”
Section: Discussionunclassified